Notas sobre a sociedade simples no novo código civil - Caminha, Uinie (2006)
The Civil Code of 2002 brought to its context the Brazilian corporate legislation, regulating long established corporate types and creating a new one: the “ordinary partnership”. This corporate type has given rise to several doubts as to its legal discipline, concerning either its name, since it might be confused with the kind of activity developed by the partnership, and the Civil Code provisions related to it, for one may find serious inconsistencies among them. The objective of this essay is to point out such problems and suggest constructions that might be able to solve them.